2019
DOI: 10.1177/1934578x19864005
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Essential Oil in Rosmarinus officinalis Leaves in Sardinia

Abstract: Rosmarinus officinalis L. is an aromatic plant belonging to the Lamiaceae family widely distributed in the Mediterranean area. The interest on this species is related to the multiple uses of the plant as a food ingredient, in the pharmaceutical and cosmetic industries. The chemical composition of essential oil (EO) from 5 accessions of R. officinalis L., collected monthly through a full year in Sardinia, has been studied by gas chromatography (GC) and GC-mass spectrometry technique. The EO ranged from 0.29% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
(63 reference statements)
3
28
0
Order By: Relevance
“…In the study at Balıkesir [67], Fethiye [68], and Kahramanmaraş [66], in the essential oil compositions of rosemary were determinated limonene, sabinene, and ocimene, while they were not found in our study. Essential oil of R. officinalis from Tunisia [56,60,68], Pakistan [11], Lebanon [57], and Belgrade [69,70], shows a high content of 1,8-cineole, while the essential oil of R. officinalis from Iran [58,71], Spain [72], Italy [20,73], Morocco [59] shows low content of this molecule, and yields a high concentration of αpinene instead; essential oil of R. officinalis from Brazil [54], in its turn, has a high concentration of camphor. These data indicated that the chemical composition variation due to the geographical area, edaphic features, and altitude where the plant is collected.…”
Section: Resultsmentioning
confidence: 99%
“…In the study at Balıkesir [67], Fethiye [68], and Kahramanmaraş [66], in the essential oil compositions of rosemary were determinated limonene, sabinene, and ocimene, while they were not found in our study. Essential oil of R. officinalis from Tunisia [56,60,68], Pakistan [11], Lebanon [57], and Belgrade [69,70], shows a high content of 1,8-cineole, while the essential oil of R. officinalis from Iran [58,71], Spain [72], Italy [20,73], Morocco [59] shows low content of this molecule, and yields a high concentration of αpinene instead; essential oil of R. officinalis from Brazil [54], in its turn, has a high concentration of camphor. These data indicated that the chemical composition variation due to the geographical area, edaphic features, and altitude where the plant is collected.…”
Section: Resultsmentioning
confidence: 99%
“…In plants, the final composition of the mixture of bioactive molecules varies depending on the geographical origin, the part of the plant used, the stage of development at the time of harvest, and the type of material used (dry leaves, green leaves, flowers, etc.) [15,35,45,46,50,51], as well as the type of extraction. This seems obvious and is confirmed in many cultivated plants [52].…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…In the volatile essential oil of rosemary, up to 150 different compounds have been found (the frequently reported molecules are 1,8-cineole, α-pinene, and camphor), with most of them being monoterpenes [11]. On the other hand, three different chemotypes can be differentiated: cineoliferum (with a high percentage of 1,8-cineole), camforiferum (with more than 20% camphor), and verbenoniferum (with more than 15% verbenone) [15,46]. There is a large body of scientific literature in which the chemical composition of rosemary is discussed [9,11,15,23,37,[46][47][48], and this is increasing as more sophisticated methods of analysis are used to examine extracts [49].…”
Section: Phenolic Acidsmentioning
confidence: 99%
See 2 more Smart Citations